RETRACTION NOTICE TO “Examining Senior High School Teachers’ Per-ceived Readiness in Online Teaching” - Santillan Jr., Eduardo P. (Future Science / FSH-PH Publications, 2023)
This article entitled “Examining Senior High School Teachers’ Perceived Readiness in Online Teaching” (2023), authored by Eduardo P. Santillan Jr, published in Vol. 4, No. 2 of International Journal of Multidisciplinary: Applied Business and Education Research. 4(2), 487 – 500 has been retracted as requested by the authors.